'That there be no black brotherhood': the failed suppression of Afro-Mexican confraternities, 1568–1612. (3rd April 2021) - Valerio, Miguel A.
ABSTRACT: This essay discusses Mexican colonial officials' efforts to suppress Afro-Mexican confraternities, or lay Catholic brotherhoods, between 1568 and 1612, a period of black confraternal activity in Mexico that has not received scholarly attention. Colonial officials – from the viceroy to royal magistrates to Church and city officials – suspected that Afro-Mexicans used brotherhoods to disguise unorthodox and criminal activities, including planning slave revolts. Sources analyzed here are the earliest records of Afro-Mexican confraternities, which allow us to study them in the sixteenth century. Thus, this essay reperiodizes the conversation about Afro-Mexican confraternities and colonial officials' suspicions of Afrodescendants' motives. The article contends, as scholars of black confraternities have sustained, that rather than the dangerous, immoral, and unorthodox places that colonial officials imagined, Afro-Mexican confraternities were instead spaces where creole black Mexicans sought to ameliorate their coloniality by forming community, pooling their resources together to care for each other in time of need, and expressing their Afro-Catholic identity through devotion and festive practices.